Achievement of Tolerance Induction to Prevent Acute Graft-vs.-Host Disease - Thangavelu, Govindarajan; Blazar, Bruce R. (Frontiers in Immunology, 2019)
Acute graft-vs.-host disease (GVHD) limits the efficacy of allogeneic hematopoietic stem cell transplantation (allo-HSCT), a main therapy to treat various hematological disorders. Despite rapid progress in understanding GVHD pathogenesis, broad immunosuppressive agents are most often used to prevent and remain the first line of therapy to treat GVHD. Strategies enhancing immune tolerance in allo-HSCT would permit reductions in immunosuppressant use and their associated undesirable side effects. In this review, we discuss the mechanisms responsible for GVHD and advancement in strategies to achieve immune balance and tolerance thereby avoiding GVHD and its complications.